Work–family interface and job satisfaction: The role of affective commitment - Gabini, Sebastián (2020)
Objective: this research was to analyze if any of the types of organizational commitment mediated the relationship between work–family interface and job satisfaction. To that end, an empirical, quantitative and cross-sectional study was designed, framed within the guidelines of an associative–explanatory approach. Method: the study variables were measured using a set of validated instruments with adequate psychometric properties. The study population consisted of a non-probabilistic convenience sample of 376 workers (191 males and 185 females) from third-sector organizations, due to their importance in the current working world. Results: the results showed that affective commitment partially mediates the relationships between the dimensions work–family interface (enrichment and conflict) and job satisfaction. This type of commitment emerges as a mediational construct between job satisfaction and the possibilities of dealing with the demands from different vital spheres. Such mechanism may be explained through the role stress theory and the social exchange theory. Conclusions: these findings might be useful when it comes to designing family– friendship policies in order to retain human talent and promote affective bonds between employees and organizations. Authorship contribution The work has been carried out entirely by the Author.